Integration of Artificial Intelligence in Learning Islamic Cultural History Through the Samr Model in the Independent Curriculum at the MTs Level - Firdah Ni'matus Sholihah; Abdulloh Hamid; Syaifuddin Syaifuddin (Universitas Islam Negeri Sumatera Utara, 2026)
The development of artificial intelligence (AI) provides significant opportunities for innovation in Islamic Religious Education (PAI) learning media, particularly in the subject of Islamic Cultural History (SKI). This article aims to analyze and conceptually develop AI-based PAI learning media integrated with the SAMR (Substitution, Augmentation, Modification, Redefinition) model and aligned with the principles of the Independent Curriculum. This research uses a descriptive qualitative approach with a literature review method, which examines various national and international research results regarding AI integration, the SAMR model, and PAI learning innovation. The study results indicate that the application of AI in SKI learning, such as the use of educational chatbots, automated videos based on historical texts, and augmented reality simulations, can increase student participation, understanding, and creativity. The integration of the SAMR model facilitates a shift from using technology as an aid to a transformational learning tool. At the Redefinition level , AI is able to redefine the learning experience by enabling students to interact virtually with the context of Islamic history. The application of AI in SKI learning is also in line with the spirit of the Independent Curriculum, which emphasizes flexibility, contextual learning, and the development of teachers' digital competencies. Thus, AI-based learning media has the potential to be a strategic solution in improving the quality of Islamic Education learning in an adaptive, creative, and future-oriented manner.